Stress Wave Propagation and Energy Absorption Properties of Heterogeneous Lattice Materials under Impact Load - Cun Zhao; Meng Zhang; Guoxi Li; Dong Wang (Advances in Materials Science and Engineering)
A heterogeneous lattice material composed of different cells is proposed to improve the energy absorption capacity. The heterogeneous structure is formed by setting layers of body-centered XY rods (BCCxy) cells as the reinforcement in the body-centered cubic (GBCC) uniform lattice material. The heterogeneous lattice samples are designed and processed by additive manufacturing technology. The stress wave propagation and energy absorption properties of heterogeneous lattice materials under impact load are analyzed by finite element simulation (FES) and Hopkinson pressure bar (SHPB) experiments. The results show that, compared with the GBCC uniform lattice material, the spreading velocity of the stress of the (GBCC)3(BCCxy)2 heterogeneous lattice material is reduced by 18.1%, the impact time is prolonged 27.9%, the stress peak of the transmitted bar is reduced by 34.8%, and the strain energy peak is reduced by 29.7%. It indicates that the heterogeneous lattice materials are able to reduce the spreading velocity of stress and improve the energy absorption capacity. In addition, the number of layers of reinforcement is an important factor affecting the stress wave propagation and energy absorption properties.